Pengaruh Kualitas Produk, Persepsi Harga dan Word of Mouth Terhadap Keputusan Pembelian Pertamax di Kabupaten Pati - Fannalif, Sega; Oktavia, Vicky; Purusa, Nanda; Perdana, Tito (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to examine how product quality, price perception, and word of mouth (WoM) communication influence Pertamax (RON 92) purchasing decisions at a Pertamina gas station in Pati Regency. The approach used is quantitative with data collection through a questionnaire involving 100 respondents. The sampling technique used is non-probability sampling with a purposive sampling method, where respondents are selected based on certain criteria relevant to the study. The collected data were then analyzed using SPSS 25 to test the relationship between variables. The results of the study indicate that product quality and price perception have a significant positive influence on Pertamax purchasing decisions by consumers. In addition, the Word of Mouth (WoM) communication factor is also proven to have a significant positive impact in encouraging purchasing decisions. These findings indicate that product quality, good price perception, and word of mouth recommendations are important factors in influencing consumers in choosing Pertamax at Pertamina gas stations.